Anti-cancer on carrageenan from red algae: Anti-kanker pada carrageenan dari alga merah - Ema Yusuf; Dian Rafika Sari D; Melinda Herman; Meuthia Narissa Azzahra; Surianti Alimin; Irene Edith Rieuwpassa (Makassar Dental Journal PDGI Makassar, 2023)
Cancers are serious diseases with various etiologies mainly due to unhealthy dietary habits and lifestyles. However, almost all drugs used for anti-cancer therapy are usually toxic and generally affect normal healthy cells, hence the search for new com-pounds that are effective, non-toxic and natural. In particular, algae contain many valuable components with great anti-cancer potential. Carrageenan is a general term describing a group of sulphated polysaccharides in red algae that present a major com-ponent of the cell wall and interstitial space functioning as a forming compound and providing intercellular adhesion and inter-cellular signalling. Carrageenan isolated from red algae has been the object of drug discovery over the past few decades as it exhibits anti-cancer capabilities.